Implementation of Anti-Corruption Values in Islamic Education Perspective - Busiri (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the implementation of anti-corruption education values in Islamic Religious Education subjects in Schools in Indonesia. This research uses a qualitative method by collecting data in the form of a literature study. The results of this study found that Islamic Religious Education can be used as a means of preventive and anticipatory efforts in developing anti-corruption values for the prevention and eradication of corruption. Islamic values embodied in anti-corruption education can be developed in the Islamic Religious Education curriculum.